2017
DOI: 10.1111/inr.12410
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on hand hygiene knowledge and compliance in student nurses

Abstract: The findings of this review emphasized the role of nurse educators in enhancing hand hygiene competence in nursing students. Implementation of empirically tested strategies such as utilizing multidimensional interventions, scenario-based hand hygiene simulation activities and hand hygiene education programmes that would enhance nursing students' hand hygiene knowledge and compliance is an asset. Hospital and nursing administrators should ensure continuous support and monitoring to guarantee that hand hygiene p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 48 publications
3
72
1
6
Order By: Relevance
“…A majority of students (98.3%) received hand hygiene training; however, mean scores on knowledge, attitude and practice were only moderate after participation in the practicum. The present findings are consistent with other research demonstrating a moderate level of hand hygiene knowledge for students in developing countries (Ariyarathne et al ; Arthi et al ; Labrague et al ; Mahadeo & Vaishali ; Paudel et al ) suggesting current hand hygiene training for healthcare students in Cambodia may not be effective or students need to have hand hygiene frequently reinforced during clinical experiences.…”
Section: Discussionsupporting
confidence: 92%
“…A majority of students (98.3%) received hand hygiene training; however, mean scores on knowledge, attitude and practice were only moderate after participation in the practicum. The present findings are consistent with other research demonstrating a moderate level of hand hygiene knowledge for students in developing countries (Ariyarathne et al ; Arthi et al ; Labrague et al ; Mahadeo & Vaishali ; Paudel et al ) suggesting current hand hygiene training for healthcare students in Cambodia may not be effective or students need to have hand hygiene frequently reinforced during clinical experiences.…”
Section: Discussionsupporting
confidence: 92%
“…However, it fits to findings reported in literature. 6,7 We found that females had a better overall knowledge regarding hand hygiene. This phenomenon was also recently reported for hand hygiene adherence in a hospital setting.…”
Section: Discussionmentioning
confidence: 72%
“…In an Irish study using WHO's tool for hand hygiene observations, they found 91.0% hand hygiene adherence among nursing students (Kingston, O'Connell, & Dunne, ), and the adherence by nursing students in another study from a university hospital in Norway was at 83.5% (Sundal et al, ). However, a systematic review revealed a low‐to‐moderate knowledge of, and compliance with, hand hygiene among nursing students (Labrague, McEnroe‐Petitte, van de Mortel, & Nasirudeen, ). These results emphasise the need for improving training programmes targeting hand hygiene practices among nursing students.…”
Section: Discussionmentioning
confidence: 99%